Smoking at home is strongly associated with symptoms of asthma and rhinitis in children of primary school age in Trinidad and Tobago - Monteil, Michele...[et al.] (2004)
Compares the prevalence of symptoms of asthma and rhinitis among children of primary school age who are exposed to household environmental tabacco smoke with the prevalence of these symptoms in their colleagues without this exposure.